Pengembangan Ekonomi Kreatif Melalui Peningkatan Value Komoditi Unggulan Desa Pasir Kecamatan Bodeh Kabupaten Pemalang - Mohammad Rosyada; Lutfiyanah Lutfiyanah; Nafsiyah Nafsiyah (Pusat Riset dan Inovasi Nasional, 2023)
This community service activity aims to grow the economy of the people of Pasir Village through developing the village's creative economy by increasing the value of corn which is the main commodity of Pasir Village into processed products that are more valuable, namely corn tortilla chips which can be marketed to various regions in Indonesia and even abroad. The method used is to conduct training on tortilla production and business managerial processes starting from operations, marketing, financial management as well as monitoring and business assistance. The results achieved from this service activity are the formation of assisted business groups that have been able to independently produce corn tortilla chips which are marketed offline and online through social media and marketplaces. This service activity is expected to be able to develop this corn tortilla product to become a superior product of Pasir Village which has a higher economic value than ordinary corn products and has an effect on creative economic growth and an increase in the income of the people of Pasir Village in a sustainable manner.